P347 Vedolizumab as first line biologic therapy in elderly patients with contraindications against anti-TNF therapy - A real-world nationwide cohort of patients with inflammatory bowel diseases. (27th May 2021) - Attauabi, M; Höglund, C; Fassov, J; Pedersen, K B; Bansholm Hansen, H; Wildt, S; Dam Jensen, M; Neumann, A; Lind, C; Albæk Jacobsen, H; Popa, A M; Kjeldsen, J; et al.
Abstract: Background: Data regarding the efficacy and safety of vedolizumab as the first line of biologic therapy for elderly patients with ulcerative colitis (UC) and Crohn's disease (CD) or patients with contraindications against anti-tumor necrosis factor antagonists (anti-TNFs) are scarce. Therefore, we aimed to investigate the short and long-term efficacy and safety of vedolizumab in patients with bio-naïve UC and CD stratified according to age. Methods: A Danish nationwide cohort study was conducted between November 2014 and November 2019, including all bio-naïve patients receiving vedolizumab. The primary outcomes were clinical remission, steroid-free clinical remission, and sustained clinical remission defined as clinical remission at week 14 through week 52. Elderly patients were defined as patients aged 60 years or older at initiation of vedolizumab. Results: The study included 56 patients (UC: 31 (55.4%), CD: 25 (44.6%)) with 15 (60.0%) and nine (47.4%) elderly patients with UC and CD, respectively. Elderly patients with UC and CD experienced higher rates of early response, remission, and steroid-free clinical remission, which, however, did not reach statistical significance (Figures 1 and 2). However, elderly patients with CD had similar long-term response as compared with younger patients. In the overall study population, lack of remission at week 52 was associated with female gender ( p =0.01) in UC and ileal CD ( p =0.03). Discontinuation due to primary non-response occurred in 20.0% and 5.3%, while rates of secondary loss of response were 12.0% and 5.3% after 26 weeks and 52 weeks, respectively. Only one UC patient, who developed a serious infection, experienced a serious adverse event during treatment with vedolizumab. However, mild adverse events were experienced by 35.5% and 8.0% of patients with UC and CD, respectively. As shown in Table 1, elderly patients experienced adverse events similar to the corresponding younger patients. Conclusion: Vedolizumab is effective for induction of short and long-term sustained clinical remission in bio-naïve elderly and younger UC and CD patients with contraindications to anti-TNFs.